Software architecture hour with Neal Ford. (O'Reilly Media, Inc., 2022)
When you think of programming languages, you probably think of Java, Kotlin, JavaScript, or Python, not CSS, SQL, or HTML. And you may not even have heard of Alloy, Modelica, or SNOBOL. But all are identified as languages, even if they're not generally considered as such. So what are the distinctions among them? And maybe most importantly, what can programmers learn from "not programming languages"? Join us for a special conversation on programming languages with Neal Ford and Mozilla software engineer Chelsea Troy. They'll talk about what constitutes a programming language, what we can learn from questioning how we categorize things, and how to identify "assumed context" and why it matters. They'll also share some lessons learned from "domain specific" programming languages. Neal and Chelsea spend a few minutes covering the trends in software development, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Investigate what constitutes a programming language (and why it matters) See what's coming next in software architecture This recording of a live event is for you because... You want to learn about how assumed context drives decision-making. You're looking for better ways to solve the problems you face when creating software and architectures. Recommended follow-up: Read Fundamentals of Software Architecture (book) Watch Software Architecture Fundamentals Beyond the Basics (video) Attend Architecture: The Hard Parts (live event).